Corynoline alleviates renal ischemia-reperfusion injury by enhancing Nrf2/HO-1 pathway - Ming Chang; Buhe Sichen (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: The potential of corynoline in ameliorating oxidative stress and inflammatory responses has been extensively demonstrated across various diseases. However, its specific role in the context of renal ischemia-reperfusion (IR) injury remains elusive. The aim of this study was to investigate the role of corynoline in renal IR injury and its mechanism. Methods: A rat model of renal IR injury was successfully developed. Samples of kidney tissue and blood were obtained to evaluate alterations in tissue damage, inflammatory response, oxidative stress, and apoptosis. Results: Corynoline significantly reduced renal IR injury, thus leading to improved renal function and mitigated tissue structure damage and cell apoptosis. Moreover, corynoline effectively suppressed the oxidative stress and inflammatory response induced by IR by increasing the superoxide dismutase (SOD) content, reducing the malondialdehyde (MDA) level, inhibiting neutrophil infiltration, and suppressing the release of proinflammatory cytokines. Mechanistically, corynoline successfully restored the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1), which were significantly inhibited during renal IR injury. Furthermore, when coadministered with ML-385 (an Nrf2 inhibitor), the protective effect of corynoline against renal IR injury was counteracted. Conclusion: Corynoline protects against renal IR injury by suppressing oxidative stress, inflammatory responses, and apoptosis, and its mechanism of action may involve the activation of the Nrf2/HO-1 pathway.